Actualité d’Albert Camus sur la scène espagnole - Rafael Ruiz Álvarez (Carnets)
In this paper we aim to pay tribute to Albert Camus by studying its presence in the most recent Spanish drama. For our purposes, we have chosen Caligula, one of his pieces which have been reinterpreted more often by Spanish playwrights. We will unveil the keys of the reiterpretation of this text by some directors; we will also observe the way the literary text is transformed into a theatrical even; finally, we will pay attention to the issues of its cultural and temporal adaptation.